Ethical Implications and Ramifications in the Case of Truong My Lan - Edgar Manuel Cambaza (REVES - Revista Relações Sociais)
This article examines the ethical and systemic failures surrounding the massive financial fraud orchestrated by Vietnamese real estate tycoon Truong My Lan. This study aims to analyze the intricate web of relationships, rights, duties, and potential responses to prevent such unethical practices in the future. Using a case study approach, the research critically evaluates the most appropriate responses and considers future preventive measures. The study draws on various scholarly sources and legal frameworks, including the Vietnamese Enterprise Law, the Labor Code, and international conventions such as the United Nations Convention Against Corruption. Findings suggest that strengthening regulatory oversight, enhancing corporate governance, and fostering a culture of transparency and accountability are crucial steps in addressing and preventing financial fraud. The research also highlights the importance of technological integration, public education, and international collaboration in building a resilient financial system. This study contributes to the broader discourse on business ethics and corporate governance by comprehensively analyzing one of Vietnam's most prominent fraud cases and proposing actionable measures to mitigate similar risks in the future.